A MULTI-PERSPECTIVE EVALUATION OF TEACHING SKILLS OF ELT STUDENT TEACHERS - Seçil Horasan Doğan; Paşa Tevfik Cephe (Informascope, 2017)
Reflective practices in teacher education programs can play a critical role in enhancing the teaching quality. However, since student teachers' self-evaluations are not adequate on their own, they need to receive as much feedback as possible from other sources. In this study, a multi-perspective evaluation was provided to contribute to the teaching skills of student teachers. To this end, 15 ELT student teachers took part in an extra-curricular project to teach 1 lesson in a language classroom. Each lesson was recorded and evaluated first by themselves, then by the language learners in this classroom, and finally by 3 trainers based on the recordings using Teacher Evaluation Form. In addition, discussion sessions with each student teacher were held to share the multi-perspective evaluation and detect its contributions. The results of the quantitative and qualitative data analysis revealed that student teachers' self- evaluations were significantly different, yet they were lower than others unlike what was hypothesized. In addition, this reflective process contributed to their reflective skills, teaching skills, and self-awareness for their professional development.